2014
DOI: 10.1186/1756-0500-7-498
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal iron and folic acid supplementation use by pregnant women in Khartoum, Sudan

Abstract: BackgroundAnaemia during pregnancy can lead to adverse maternal and perinatal outcomes. The WHO recommends that all pregnant women in areas where anaemia is prevalent receive supplements of iron and folic acid. However, due to many factors, the use of iron and folic acid supplementation is still low in many countries. This study was conducted to assess the rates of iron-folic supplementation and the associated factors during pregnancy and the effects of taking iron-folic acid supplementation on rates of matern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
53
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 16 publications
12
53
4
Order By: Relevance
“…In the case of anaemia in women, there was no effect of the programme in the individual or district-level analyses. Juntos could prevent anaemia by requiring pregnant women to attend antenatal visits where iron supplementation is provided (Abdullahi et al 2014). As a small proportion (6.1% for the individual level and 5.5% for the district level analyses) of the women included in this study were pregnant, the effect of antenatal visit attendance was probably diluted.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of anaemia in women, there was no effect of the programme in the individual or district-level analyses. Juntos could prevent anaemia by requiring pregnant women to attend antenatal visits where iron supplementation is provided (Abdullahi et al 2014). As a small proportion (6.1% for the individual level and 5.5% for the district level analyses) of the women included in this study were pregnant, the effect of antenatal visit attendance was probably diluted.…”
Section: Discussionmentioning
confidence: 98%
“…Number of studies revealed that maternal education is positively associated with utilization of prenatal iron supplementation. According to studies in Amhara region [10], Ethiopia [8], Khartoum [18], Rio de Jenerio [19] and India [20], illiterate women had reduced odds of using prenatal iron supplementation as compared to women who can at least write and read. A current study also showed the same direction of association between these variables.…”
Section: Discussionmentioning
confidence: 99%
“…As witnessed by several studies, utilization of prenatal iron supplementation increases with increasing frequency of ANC visits. Studies undertaken in Rio Grande [22], Tanzania [21], Khartoum [18], Tigray [23] and four major regions of Ethiopia [9] found that increased ANC visit enhance increased use of iron tablets. The current study showed consistent results; women who had ANC lower than four visits had reduced odds of using prenatal iron supplementation than those who had four plus ANC visits.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that micronutrient deficiency is a global public health problem affecting two billion people worldwide (10,18), of which million are women in their reproductive age (19). Although diet related health problem affects both sexes and all age groups, it is a major public health problem among women (20) especially among adolescent girls (21).…”
Section: Introductionmentioning
confidence: 99%